ACCOUNTING INFORMATION SYSTEM DESIGN FOR MUTIARA MARTA WAREHOUSE STORE - admin, NINDY VIRNALIA B42111021 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
Development of the globalization make the business men needs accounting information system in order to easier running their business, there is no exception for small and medium enterprises (SMEs). With accounting information system a company could aware about the profit and loss of the company. Information system is also useful to identify problems that occur in the company. Accounting information system helps the entity for planning, controlling, and decision making. Mutiara Marta Warehouse store is a trading company that engages in the purchasing and selling of building materials. The whole system at the company is still using a manual system where the transaction is done every day, but there is no bookkeeping for saving the data transactions of the company. This is also added with no sufficient inventory, which makes the owner sometimes finding difficulties to know the inventories flow. This research tried to arrange the adequate accounting information system which is needed in this entity. The purpose of this accounting information system arrangement is to provide the accurate and up to date data. The design of the new system starts with analysis the current systems at the company. The main activities in this store are classified to revenue, expenses, and inventory, then the author would make the accounting information system design for these three main cycle. Information system which designed for this warehouse store covers the accounting data processing including purchase and sales. So the output of this research is managerial report consist of purchase reports, sales reports, account payable, and account receivable. At the end all the data then reported in financial management under SAK ETAP. Â  Keywords: Accounting Information System, Small and Medium Enterprises (SMEs), SAK ETAP. Â